Ethnopharmacology Study Of Medicinal Plants Used By Batak Community In Pasaribu Tobing Sub-District Of Tapanuli Tengah District Of North Sumatra Province - Dewy Resty Basuki; Prihardini Prihardini; Rosa Juwita Hesturini (Jurnal EduHealth, 2023)
Ethnopharmacology is an effort to explore and discover new compounds in natural products that are related to the use of traditional medicines that apply to certain ethnic groups. These study has been conducted of ethnoparmacology medicinal plants that utilized the Batak community in Pasaribu Sub District Tobing District Central Tapanuli North Sumatra Province. Methods of this study include observational studies and ethnopharmacology studies. The results showed that the plants that are used as medicine in Pasaribu Tobing Subdistrict include 36 tribes consisting of 61 species, with the most commonly used tribe is Zingiberaceae of 9.83%. The most popular medicinal plants are used as antiseptics. The leaves are part of the most stout plants in use by 41.79%. The treatment of medicinal plants is mostly done by boiling 33.33% and the use of medicinal plants are the most widely used by drinking method by 56.61%.